(untitled) (Swiss Medical Weekly, 2022)
AIMS OF THE STUDY: This study set out to examine the association between current subspecialty (paediatric and hand surgery) consultation practice for children with hand and finger injuries presenting to a tertiary paediatric emergency department and length of stay in the paediatric emergency department. Also, incidence and injury pattern of hand and finger injuries in this patient group were analysed. METHODS: This was a retrospective cross-sectional study, which was undertaken as a clinical audit service. All patients under 17 years presenting to our paediatric emergency department with hand and finger injuries over a 17-month period were included in the analysis. We studied incidence and injury mechanism, current subspecialty referral practice, as well as paediatric emergency department and hospital length of stay. RESULTS: We identified 929 children for inclusion in the analysis. The most frequent reasons for presentation were hand contusions (25.5%) and fractures (20.8%). Paediatric emergency medicine physicians alone managed 845 patients (90.6%), paediatric surgery referral occurred in 50 (5.4%) and hand surgery consultation in 37 (4.0%) cases. Mean length of stay in the paediatric emergency department was 154 min and significantly longer when subspecialty review occurred. Hospital admission occurred in 87 cases (9.3%). CONCLUSIONS: Involvement of subspecialties in the care of hand and finger injuries was associated with significantly increased length of stay in the paediatric emergency department. We discuss obstacles and enablers for timely patient referral and management. We suggest the implementation of referral guidelines, tailored to the individual emergency department, to reduce unnecessary patient journey delays and to ensure higher quality repair of complex hand injuries by the appropriate surgeon, with better outcomes. Making use of the emergence of multiple surgical subspecialties for targeted treatment of paediatric finger and hand injuries might be desirable.